Solar panel inspection techniques and prospects. (15th March 2023) - Meribout, Mahmoud; Kumar Tiwari, Varun; Pablo Peña Herrera, Juan; Najeeb Mahfoudh Awadh Baobaid, Asma
Abstract: Global awareness of environmental issues has spurred wide interest in renewable energy resources, among which solar energy is one of the most attractive of these alternatives. Nevertheless, for these plants to operate effectively, high-quality installations, regular maintenance, and detailed inspections are required. The purpose of this paper is to review different monitoring techniques of large photovoltaic (PV) plants. They can be categorized into cameras or non-cameras-based techniques which both yield complementary information. Indeed, the paper shows that up-today, there is no sensing technique which is adequate to operate in all conditions or to satisfy all possible constraints. For instance, while cameras allow quick contactless and non-destructive monitoring, other techniques yield more accurate information on the types of faults. Advances in unmanned aerial vehicles and edge processors gave wider monitoring opportunities by significantly exhibiting the process while accurately providing the location of the faults. The topic addressed in this paper is critical for years to come since several kinds of faults may occur frequently causing substantial power losses and, in some cases, raising serious safety threats. This has motivated some researchers to issue related review papers. Nevertheless, this paper addresses the state-of-the-art technique for every type of fault in addition to explain the concepts of most recent sensors. This is required to grasp the methodologies implemented to satisfy the underlined accuracy and safety constraints. For instance, the paper lists five different kind of voltage/current sensors having different accuracy levels and suggest their adequate placement within the PV plants. In addition to different intellectual property works which were disclosed in patents, the paper also exhibits several commercially available inspection instruments, in addition to most recent industrial achievements and real-field experience. Most of the current review papers mainly focused on academic works.